Cotton Growth and Development - David L. Wright; Isaac Esquivel; Sheeja George; Ian Small (EDIS)
Management of cotton requires an understanding of the growth habit and responses of the plant to the environment. This publication provides basic information for understanding how a cotton plant develops and some of the factors that can alter the pattern of development. This document is SS-AGR-238, one of a series of the Agronomy Department and the North Florida Research and Education Center, Quincy FL. Original publication date February 2005. Updated May 2022 by David L. Wright, Isaac Esquivel, Sheeja George and Ian Small.